Traffic Light Design with Infrared Sensors - Meiyanto Eko Sulistyo; Feri Adriyanto; Royani Aulia Ihsanti (Universitas Sebelas Maret (UNS), 2022)
The development of Traffic Light Design with Infrared Sensors is done to accommodate about how many vehicles may pass through each lane in inersections. The traffic light is using infrared sensors at each lane to measure the density of vehicles. Infrared sensor then sends those data to micro-SD card module to be stored. Arduino Mega will receive data from infrared and real-time clock module about how many vehicles and what time they were counted to then display it on liquid crystal display. A detailed description of each component, the architecture and system design of prototype has been provided. The system prototype has been simulated in Fritzing simulation software.